Self-reported hearing impairment among rural adult population of coastal Tamil Nadu - Chauhan, Ramesh Chand; Mishra, Amit Kumar; Kandan, Mani; Singh, Zile (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2015)
Background: Hearing impairment is the most frequent sensory deficit in human population and irrespective of the age of development, has devastating consequences. This study was done to assess the burden of hearing impairment among the rural adult population of a coastal area in Tamil Nadu. Methods: This community-based descriptive study was conducted in a rural area of Tamil Nadu state in India. The study protocol was approved by the institute ethics committee of PIMS. Eligible participants from all the household in the study area were selected. A semi-structured questionnaire was used to collect the information and hearing impairment was assessed by self-reporting by the participants. Proportions for categorical variables were calculated and Chi-square test was applied to find the associations. Results: Among a total of 5621 participants interviewed and examined, 232 (4.1%) participants reported to have hearing impairment. Among them, majority reported that they have hearing impairment due to advanced age or non-specific causes resulted in hard to hearing (77.6%) and 12.5% reported to have deafness. Ear discharge (4.3%), wax (3.0%) were other commonly reported cause of hearing impairment. The hearing impairment increased with age and was common among elderly. The reported hearing impairment ranges from 1.5% to 11.3% in different age groups. Age, sex, education and occupation were significantly associated with hearing impairment (p value <0.05). Conclusions: A large number of people in rural communities were having hearing impairment. Improving access to health education and raising awareness about prevention and the needs of people with hearing loss in community is required.